Corporate social responsibility as a component of sustainable development of a construction enterprise - Bielienkova, O. (Ways to Improve Construction Efficiency, 2023)
The article examines the role of corporate social responsibility (CSR) in ensuring the sustainable development of a construction enterprise. The conceptual foundations of CSR, key factors in changing the concept of CSR and the imperatives of its development and the impact on the socio-economic development of companies in the construction industry are considered. Particular attention is paid to the relationship between the implementation of sustainable development principles and the implementation of CSR strategies that take into account environmental, economic and social aspects. The article analyzes the current challenges faced by construction enterprises in the context of strengthening environmental requirements and standards, growing public expectations for responsible business conduct and competition in the market. The article identifies areas for implementing best practices for implementing CSR in the construction sector, which are recommended to be disseminated to construction participants in order to transition to the principles of sustainable development, in particular in the field of energy efficiency, waste disposal, local community development and improving the quality of jobs. Considerable attention is paid to the analysis of the benefits of implementing CSR, including strengthening the company’s reputation, increasing its competitiveness, attracting investments and increasing employee and customer loyalty. Barriers that may arise during the implementation of such initiatives are also examined, and recommendations are offered for overcoming them. The impact of CSR on the internal efficiency of a construction company deserves special attention. The application of energy efficiency principles, rational use of resources, development of human resources and social programs for employees contribute to reducing costs, increasing productivity and forming a sustainable business model. The results of the study indicate that integrating CSR into the development strategy of a construction company contributes to achieving long-term business sustainability and ensuring a balance between economic benefit, social responsibility and environmental safety. Specific steps are proposed to strengthen CSR in the construction sector, which can be adapted to different business conditions.